The operative risk stratification models in cardiac surgery: EuroSCORE II model – risk groups categorization - Nežić, Duško; Miličić, Miroslav; Petrović, Ivana; Košević, Dragana; Mićović, Slobodan (Vojnosanitetski pregled, 2021)
Background/Aim. The treshold that defines a low, moderate or high-risk patients is not uniformly determined for the European System for Cardiac Operative Risk Evaluation (EuroSCORE II) by literature at present. The aim of this study was to suggest risk groups categorization within EuroSCORE II risk statification model. Methods. A 7,641 consecutive patients were scored preoperatively using EuroSCORE II. The end point for the study was in-hospital mortality accross the risk group categories. Patients with EuroSCORE II values of ≤ 2.50, > 2.50–6.50%, and > 6.50% were defined to be at low, moderate, and high perioperative risk, respectively. Discriminative power of the model was tested by calculating the area under the receiver operating characteristic curve (AUC). The calibration of the model was assessed by Hosmer-Lemeshow statistics, and with observed/expected (O/E) mortality ratio. Results. In-hospital mortality observed in our sample was 3.85% (295 out of 7,641 patients). The EuroSCORE II discriminative power was acceptable (AUCs > 0.70) for the low and high risk groups, while it failed to confirm good discrimination in the moderate risk group. Hosmer-Lemeshow statistics confirmed good calibration across risk group categories. The O/E mortality ratio failed to confirm good calibration in the low and high risk group (slight, but significant underprediction ratio of 1.24; 95% confidence interval 1.05–1.43), but confirmed good calibration in all three subcategories of the high risk group. Conclusion. The results of this study showed an acceptable overall performance of the EuroSCORE II in terms of discrimination and accuracy of model predictions for perioperative mortality across risk group categories. Validation of EuroSCORE II performances across risk group categories needs to be further studied for a continuous improvement of patients' risk stratification before planned cardiac surgery.
Keywords: cardiac surgical procedures; hospital mortality; risk factors; risk assessment; models, theoretical; europe